2021
DOI: 10.1007/s00383-021-04992-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased incidence of intussusception during the COVID-19 pandemic. Trends in pediatric surgical emergencies

Abstract: Purpose Recent reports suggest that the COVID-19 pandemic may be influencing disease morbidity. The purpose of this study was to investigate pandemic-related changes in the incidence of pediatric surgical emergencies. Methods Data from patients with one of 8 typical conditions considered to be pediatric emergencies who presented at 3 hospitals close to central Tokyo were collated retrospectively from accident and emergency (AE) department records for 2020 and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Our study also showed that the total number of pediatric visits to EDs and patients with suspected and true intussusception also decreased. Seo S et al also reported a 3-percentage-point reduction in pediatric intussusception patients in 2020, compared to the pre-COVID-19 pandemic period, in an analysis based on data from three hospitals in Tokyo, Japan [ 25 ]. There are two possible reasons for the decrease in the number of pediatric intussusception patients visiting the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that the total number of pediatric visits to EDs and patients with suspected and true intussusception also decreased. Seo S et al also reported a 3-percentage-point reduction in pediatric intussusception patients in 2020, compared to the pre-COVID-19 pandemic period, in an analysis based on data from three hospitals in Tokyo, Japan [ 25 ]. There are two possible reasons for the decrease in the number of pediatric intussusception patients visiting the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no such studies thus far, except for one study on the COVID-19 pandemic and changes in pediatric emergency diseases, including intussusception. 21 This is significant as it is the first study to reveal the impact of infection control measures during the COVID-19 pandemic on the incidence of intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…Some later studies also documented that the COVID-19 pandemic and the implementations of preventative measures to combat this communicable disease have notably influenced the epidemiology of intussusception [ 15 , 16 , 17 , 18 ]. Meanwhile, Handa et al demonstrated that social distancing has resulted in a significant decline in intussusception [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic of COVID-19 has significantly changed the epidemiology of intussusception. Zheng et al in China were the first to report that the number of pediatric patients with intussusception decreased significantly in 2020 [ 14 ], as demonstrated by some recent studies [ 15 , 16 , 17 , 18 ]. Nevertheless, the in-depth influence of the COVID-19 pandemic on the diagnosis and treatment of intussusception for pediatric patients has not been well documented.…”
Section: Introductionmentioning
confidence: 99%